Derechos laborales en la empleabilidad de las personas con discapacidad - Sánchez Martínez, Jeniffer Paola (My University, 2020)
The purpose of this work is to analyze the incidence of labor rights on the employability of people with disabilities who reside in the Santa Rosa canton, El Oro province, based mainly on internal laws and regulations, through the document review process, it is identified the laws that protect and guarantee the full enjoyment of the right to work by this priority group, among them the Constitution of the Republic of Ecuador, the Labor Code and the Organic Law on Disability. It is worth mentioning that, despite the existence of labor rights for people with disabilities, and the effort made by the State, the reality that these people experience is different, they encounter situations that limit their full exercise in the workplace, among themselves and the most important is the ignorance of their rights, which causes them to be violated and / or discriminated against by society. However, the law is clear in obliging both public and private companies to include people with disabilities according to the number of workers with whom they are counted, in order to comply with what is stipulated in Article 11, subsection 2. All people are equal and will enjoy the same rights, duties and opportunities. Constitution of the Republic of Ecuador, 2008), it also determines the guidelines that companies must comply with so that people with disabilities physical, mental, intellectual ... etc exercise their work in optimal conditions.
El presente trabajo tiene como propósito analizar la incidencia de los derechos laborales en la empleabilidad de las personas con discapacidad que residen en el cantón Santa Rosa provincia El Oro, basándose principalmente en Leyes y normas legales internas, mediante el proceso de revisión documental, se identifica las leyes que amparan y garantiza el pleno goce del derecho al trabajo por parte de este grupo prioritario, entre ellas la Constitución de la República de Ecuador, Código de Trabajo y la Ley Orgánica de Discapacidad. Cabe mencionar que, pese a la existencia de derechos laborales de personas con discapacidad, y el esfuerzo por parte del Estado, la realidad que viven estas personas es otra, se encuentran con situaciones que limitan su pleno ejercicio en el ámbito laboral, entre ellas y la más importante es el desconocimiento de sus derechos, lo que produce que sean vulnerados y/o discriminados ante la sociedad. Sin embargo, la ley es clara al obligar tanto a las empresas públicas como privadas el incluir a personas con discapacidad según la cantidad de trabajadores con la cuente, con la finalidad de cumplir con lo que se estipula en el Art. 11 inciso 2. Todas las personas son iguales y gozaran de los mismos derechos, deberes y oportunidades. Constitución de la República del Ecuador, 2008, así mismo determina las pautas que deben cumplir las empresas para que las personas con discapacidad física, mental intelectual…etc ejerzan su labor en óptimas condiciones.
Keywords: DERECHO LABORAL; LEY; INCLUSION; DISCAPACIDAD